Decision making in mergers & acquisitions using chaos theory : an additional perspective for managers - Quek, Wei Lee (2008)
This paper introduces the Chaos Theory model as an additional perspective for managers when making merger and acquisition decisions. It is therefore meant to be a supplement to traditional decision making models when managers are assessing the suitability of a potential target. For our analysis, the Chaos Theory model is applied to mergers and acquisitions in the US software industry.